Pesantren Living Pharmacy Management Model: Cultivation of Family Medicinal Plants (TOGA) as a Response to the Global Drug Availability Crisis - Syaiful Muda'i (JM-NU: Jurnal Studi Manajemen Pendidikan Islam, 2026)
Background: The global drug availability crisis has become increasingly tangible since early 2025, with unprecedented tariffs on pharmaceutical imports, supply chain disruptions, and over 100 medicines in short supply worldwide. Approximately two billion people globally lack access to essential medicines. Islamic boarding schools (pesantren) in Indonesia face significant vulnerability to this crisis, yet possess traditional knowledge and available land that can be optimized through Family Medicinal Plants (TOGA) cultivation as a living pharmacy. Objective: This study aims to develop a management model for pesantren living pharmacy through TOGA cultivation as a strategic response to the global drug shortage crisis. Method: This qualitative study employs a grounded theory approach. Data were collected through in-depth interviews, participant observation, and document analysis involving pesantren administrators, santri, TOGA cultivation managers, and health practitioners in selected pesantren in [location]. Data analysis followed the Corbin and Strauss (2015) grounded theory procedure. Findings: The study identified three core categories: (1) the urgency of pesantren health independence amid global drug shortages, (2) the integration of TOGA cultivation into pesantren management systems, and (3) a four-phase living pharmacy management model encompassing planning, cultivation, processing, and utilization. Conclusion: A substantive theory of Pesantren-Based Living Pharmacy Management is proposed, offering a strategic framework for building health self-sufficiency in pesantren communities as a response to global pharmaceutical supply vulnerabilities.